The Implementation of Glocalization Learning Using Mayang Rontek Dance from Mojokerto to Improve Students' Science Literacy - Irsyad Yusuf Santoso; Pradipta Ramadhan Putra Wirawan; Hasan Subekti; Beni Setiawan; Maharani Agustina Arivi (Prodi S2 Pendidikan Fisika Universitas Negeri Surabaya, 2026)
This study investigates the implementation of glocalization learning using the Mayang Rontek Dance of Mojokerto to improve junior high school students’ scientific literacy. The novelty of this research lies in applying a glocalized ethnoscience approach through the Mayang Rontek Dance beyond its original cultural setting. A pre-experimental one-group pretest–posttest design was employed involving 45 students. Data were collected through validation sheets, observation sheets, scientific literacy tests, and student response questionnaires, and analyzed using descriptive statistics, a paired-samples t-test, and N-gain analysis. The results showed that the teaching modules and instructional materials were highly feasible, with most validation aspects scoring above 90%, although the student worksheet (LKPD) component obtained the lowest score (75%). The implementation of the glocalization learning model was categorized as very good. Statistical analysis revealed a significant improvement in students’ scientific literacy skills (t = 4.993, p < 0.001), with the mean score increasing from 48 on the pretest to 70 on the posttest and an N-gain value of 0.42 (moderate category). The greatest improvement occurred in students’ ability to evaluate scientific information and make decisions based on credible evidence. Student responses were highly positive, particularly regarding the systematic presentation (97.78%) and clarity of illustrations (95.56%). These findings indicate that Mayang Rontek Dance-based glocalization learning is feasible and effective for enhancing scientific literacy while supporting local cultural preservation.